Evaluation of The Basic Mentality Post-Training Program At Automotive Company In West Java - Yuliyantoro, Aris; Fikri, Aula Ahmad Hafidh Saiful (Dinasti Publisher, 2025)
This study aims to analyze the implementation of the post-training program evaluation of Basic mentality. To find out all stages of the Kirkpatrick model evaluation; reactions, learning, behavior and results, supporting and inhibiting factors and recommendations. The research method is a mixture of qualitative and quantitative with a population of 360 people and a purposive sampling technique with a sample of 51 people. Data collection techniques using interviews, questionnaires and tests. Research instruments; validity test and reliability test. Validity test results; reaction level; 0.824, learning; 0.862, behavior; 0.854 and results; 0.854, if the correlation value is above 0.30 then the instrument item is declared valid. Reliability test results; 0.946, if the Cronbach's alpha value ? 0.60, then the instrument is declared reliable. It is concluded that the training program using the on-the-job training method and the Kirkpatrick evaluation model is effective. It is recommended that the post-training program evaluation can use the Kirkpatrick evaluation model and the implementation of training can use the on-the-job training method.